35. Vestibular-coclear nerve involvement in Charcot–Marie–Tooth disease: A pilot-study. Issue 4 (April 2016) - Silipo, S.; Fabrizi, G.M.; Cavallaro, T.; Tozzi, M.C.; Monaco, S.; Bertolasi, L.
Abstract : Some authors suggested a multifactorial genesis of imbalance in patient affected by Charcot–Marie–Tooth disease (CMT) caused not only by reduced proprioceptive input but also by a vestibular impariment. Nowadays no neurophysiological studies have been performed to support this hypothesis. Aim of our pilot case-control study is to determine the prevalence of vestibular coclear nerve involvement in patients affected by CMT. Second aim is to compare the severity of vestibular coclear neuropathy among the neurophysiological subtypes of CMT (nominated as demyelinating, axonal or intermediate) or lasting of the disease. 20 patients affected by CMT (10 demyelinated, 5 axonals and 5 intermidiate forms) underwent to a neurological and neurootological examination, cVEMPs, oVEMPS, BAERS, and caloric stimulation by Fitzgerald–Hallpike standard protocol. The severity of disease was evacuate using CMT-neuropathy score 2. Preliminary data suggested an high prevalence of bilateral vestibulopathy even in the early stage of the disease.